2006
DOI: 10.1038/sj.npp.1301274
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endocannabinoids in Alcohol Consumption and Intoxication: Studies of Mice Lacking Fatty Acid Amide Hydrolase

Abstract: Endocannabinoid signaling plays the important role in regulation of ethanol intake. Fatty acid amide hydrolase (FAAH) is a key membrane protein for metabolism of endocannabinoids, including anandamide, and blockade of FAAH increases the level of anandamide in the brain. To determine if FAAH regulates ethanol consumption, we studied mutant mice with deletion of the FAAH gene. Null mutant mice showed higher preference for alcohol and voluntarily consumed more alcohol than wild-type littermates. There was no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(113 citation statements)
references
References 55 publications
(56 reference statements)
8
103
2
Order By: Relevance
“…In our experiments, URB597 was injected peripherally at doses that can inhibit FAAH activity in the whole brain (Kathuria et al 2003). Several major methodological differences can be also identified between our study and the report published by Blednov et al (2007). For example, our experiments used Wistar rats operantly self-administering alcohol or msP rats taking alcohol under limited access conditions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our experiments, URB597 was injected peripherally at doses that can inhibit FAAH activity in the whole brain (Kathuria et al 2003). Several major methodological differences can be also identified between our study and the report published by Blednov et al (2007). For example, our experiments used Wistar rats operantly self-administering alcohol or msP rats taking alcohol under limited access conditions.…”
Section: Discussionmentioning
confidence: 86%
“…The same study showed that intra-prefrontal cortex administration of URB597 increased operant alcohol self-administration in nonselected Wistars. More important, Blednov et al (2007) reported that FAAH knockout mice voluntarily consume more alcohol than wild-type littermates, while treatment with URB597 increases alcohol intake in wildtype mice. In contrast with these earlier findings, in the present study, alcohol intake was not affected by URB597 administration.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have confirmed that the rewarding effects of ethanol require CB1 receptor activation since CB1 knock out mice do not develop preferences for ethanol-paired compartments (144,159). In addition, pharmacological blockade or genetic ablation of FAAH enzymes in mice increase ethanol preference and intake in a two-bottle free-choice procedure (166,167). The prefrontal cortex and the nucleus accumbens appear two brain regions implicated in the modulation of the reinforcing effects of ethanol by cannabinoids (168,169).…”
Section: Alcoholmentioning
confidence: 89%
“…The severity of HIC is found to be lower in FAAH-KO than WT mice [56]. Conversely, Blednov et al, (2007) reported no difference in the HIC in these mice [64]. The possible explanation for this inconsistency might be due to differences in alcohol dosage administered (chronic versus acute).…”
Section: Alcoholism and Endocannabinoid Systemmentioning
confidence: 93%
“…There are a limited number of studies that have investigated the role of FAAH in alcohol drinking behavior [55,64,92]. It was reported that the mice lacking FAAH gene on a mixed genetic background (B6/129SV/J) consume significantly more alcohol compared to their WT counterparts [92].…”
Section: Role Of the Faah In Alcohol-related Behaviormentioning
confidence: 99%